Analysis of Factors That Affect The Turnover Intention of UD Maju Bersama Employees - Marlindawaty Marlindawaty (Riviera Publishing, 2025)
This research aims to analyze the factors that influence the turnover intention of UD Maju Bersama employees as a form of advice, criticism and input for the leadership of UD. Maju Bersama in managing human resources. This research uses a type of qualitative reasearch. Data collection techniques through interviews, observation and documentation. Data analysis uses data reduction, data presentation and drawing conclusions. The results of the research prove that the workload factor, wage factor and leadership style factor are important to identify the occurrence of employees who work at UD Maju Bersama. The leader should give a workload in accordance with the agreed job desc. and not give an additional workload. The wages given should be in accordance with the workload and responsibility of each employee so that employees feel fair and loyal in carrying out their work. Furthermore, the leadership style requires leaders to be able to oversee the working conditions of employees and not reduce their authority in front of his employees.